2004
DOI: 10.1016/j.neuron.2004.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Neurons Coding Suppression of Specific Saccades

Abstract: The prefrontal cortex has been implicated in the suppression of unwanted behavior, based upon observations of humans and monkeys with prefrontal lesions. Despite this, there has been little direct neurophysiological evidence for a mechanism that suppresses specific behavior. In this study, we used an oculomotor delayed match/nonmatch-to-sample task in which monkeys had to remember a stimulus location either as a marker of where to look or as a marker of where not to look. We found a group of neurons in both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
80
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 58 publications
11
80
1
Order By: Relevance
“…A possible explanation for this is that the inactivated sites corresponded to areas 46 and 9/46 (Petrides and Pandya, 1999), whereas our corticotectal neurons were recorded primarily from area 8a, anterior to FEFs. This area corresponds closely to that identified by Hasegawa et al (2004), as containing neurons coding saccade suppression.…”
Section: Discussionsupporting
confidence: 76%
“…A possible explanation for this is that the inactivated sites corresponded to areas 46 and 9/46 (Petrides and Pandya, 1999), whereas our corticotectal neurons were recorded primarily from area 8a, anterior to FEFs. This area corresponds closely to that identified by Hasegawa et al (2004), as containing neurons coding saccade suppression.…”
Section: Discussionsupporting
confidence: 76%
“…It is likely that this change between stages is associated with the neural representation of the goal through processes such as shifting of attention and vector inversion, which correspond to the encoding of a spatial location away from the stimulus (33). Similar activation by stimuli that the monkey is explicitly instructed not to foveate has been previously reported in the prefrontal cortex (43). Activity associated with vector inversion has also been reported in the Lateral Intraparietal Area (44), at least for a memory-guided antisaccade task, which allows the monkey considerable time to plan the response away from the stimulus.…”
Section: Discussionsupporting
confidence: 60%
“…Their methods did not allow them, however, to ascertain how widely these inputs were spread over the colliculi. Hasegawa et al (2004), however, found neurons in DLPFC (and to a lesser extent in FEF) that became active when a saccade to a specific object had to be suppressed. These neurons would be ideal for the implementation of location-specific inhibition as proposed here.…”
Section: Novelties and Predictionsmentioning
confidence: 86%